Jurnal Hasil Penciptaan Karya Teater Wayang Figuratif Pasung Jiwa - Premma Adhitya, I Gede Githa; Sekar Marhaeni, Ni Komang; Darma Putra, I Gusti Made (Pusat Penerbitan LP2MPP ISI Bali, 2025)
Figurative wayang is an innovation in performing arts that combines traditional elements with modern approaches to create a unique and original art form. This work introduces a new perspective in wayang art through the exploration of three-dimensional movement techniques, individual performance systems, and visual aesthetics that blend traditional and contemporary elements. The wayang puppets are designed in a surrealistic style, depicting human figures with distortion, deformation, and stylization to create a profound aesthetic effect. The creative process in crafting figurative wayang involves the development of movement techniques using specialized rods, creating the illusion of suspended puppets moving naturally. The one-puppet-one-puppeteer system provides freedom for dynamic and expressive movement exploration. Costume and accessory designs adapted from everyday life enhance the social and cultural relevance of the work, making it not only entertaining but also a reflection of life. This work also integrates elements of theater, dance, and shadow mapping projection to create an immersive aesthetic experience. These techniques strengthen the narrative and evoke a deep dramatic atmosphere, effectively conveying moral messages and life values in an inspiring way. With its innovative approach and integration of diverse artistic elements, figurative wayang becomes a form of performing art that not only preserves tradition but also offers relevant updates in line with contemporary developments. This work is expected to inspire artists to continue evolving wayang art as a dynamic and living cultural heritage.